Towards a SAR system for snow and land ice applications - Rott, H; Domik, Gitta; Mätzler, C; Miller, H (ESA Proceedings of a Workshop on Thematic Applications of SAR DATA p 29-39(SEE N 86-28488 19-42))

Architekten- und Künstlerbiographien - Seng, Eva- Maria (Ehrwürdige Zeugen verschwundener Tage, Tübinger Baudenkmale in Architekturzeichnungen des 19. Jahrhunderts, Katalog zur Ausstellung Tübingen 1986 (Tübinger Kataloge Nr. 29))

Die Zeichner und die Art der Darstellung - Zur Entwicklung und Funktion der Architekturzeichnung im 19. Jahrhundert - Seng, Eva- Maria (Ehrwürdige Zeugen verschwundener Tage, Tübinger Baudenkmale in Architekturzeichnungen des 19. Jahrhunderts, Katalog zur Ausstellung Tübingen 1986 (Tübinger Kataloge Nr. 29))

Die deutschsprachige Literatur Osteuropas und ihre Rezeption in der Bundesrepublik. Probleme und Chancen einer 'kleinen Literatur' - Eke, Norbert Otto (Deutsche Studien 29)
Auch erschienen in: Neue Zeitung [Budapest], Nr 28 vom 14.7.1990, S. 6-7, und Nr 29 vom 21.7.1990, S. 8-9, sowie Neue Literatur [Bukarest], H. 5-6/1990/91, S. 22-42

Improvements in Connected Digit Recognition Using Linear Discriminant Analysis and Mixture Densities - Haeb-Umbach, Reinhold; Geller, Dieter; Ney, Hermann (ICASSP, Minneapolis)
Four methods were used to reduce the error rate of a continuous-density hidden Markov-model-based speech recognizer on the TI/NIST connected-digits recognition task. Energy thresholding sets a lower limit on the energy in each frequency channel to suppress spurious distortion accumulation caused by random noise. This led to an improvement in error rate by 15%. Spectrum normalization was used to compensate for across-speaker variations, resulting in an additional improvement by 20%. The acoustic resolution was increased up to 32 component densities per mixture. Each doubling of the number of component densities yielded a reduction in error rate by roughly 20%. Linear discriminant analysis was used for improved feature selection. A single class-independent transformation matrix was applied to a large input vector consisting of several adjacent frames, resulting in an improvement by 20% for high acoustic resolution. The final string error rate was 0.84%.

The Development of Ernst Schröder’s Attitude towards Logic [Abstract] - Peckhaus, Volker (XIXth International Congress of History of Science. 22–29 August 1993 Zaragoza (Spain). Book of Abstracts Symposia)

Heiner Müller - Eke, Norbert Otto (Deutsche Dichter des 20. Jahrhunderts)

Michael Hamburgers Übersetzungen und einige neue Tendenzen in der englisch-sprachigen Hölderlin-Rezeption - van Laak, Lothar; Bartels, Kathrin; Brenig, Claudia; Prudlo, Marion (Hölderlin-Jahrbuch 29)

Contributions of Bound and Unbound Two-Exciton States to the Nonlinear Optical Response of GaAs Quantum Wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bennhardt, D.; Schulze, A.; Thomas, P.; Hey, R.; Ploog, K. (International Conference on Ultrafast Phenomena)
The strong influence of exciton/exciton interaction on the nonlinear optical response of the 2D exciton in GaAs quantum wells has been demonstrated in several recent experimental studies. The theoretical model for the microscopic coupling mechanism is still the subject of controversy, however. In ref. [1], we have presented a model including a density dependent coupling between opposite spin excitons which assumes that the interaction results in a renormalization of the matrix elements, dephasing rates and energies of the transition from the single-exciton state to the two-exciton state with respect to the corresponding quantities for the single exciton transitions. In contrast, Wang et al. claim that all experimental observations are explained by a density induced dephasing rate and that biexciton states play no role [2]. Here we present a new 3-pulse degenerate-four-wave-mixing (DFWM) configuration which is able to differentiate between pure local field effects and biexcitonic contributions to the time-integrated signal. Experiments were performed on an almost homogeneously broadened GaAs/Al0.3Ga0.7As single QW (well width 20 nm, photoluminescence line 0.3 meV, homogenous linewidth 0.15 meV) in the backward reflection geometry. The sample was cooled to 10 K and excited by a sequence of three pulses (1.1 ps duration) with equal intensity, wave vectors 𝑘→1,𝑘→2,𝑘→3 and delays τ12 and τ13 between the second and first and the third and first pulse, respectively. The signal was monitored in the direction 𝑘→𝑠=𝑘→1+𝑘→2−𝑘→3 which provides no signal for the chosen pulse length if local field and renormalization effects are negligible. The peak intensity of the time-integrated DFWM signal has been calculated by solving the optical Bloch for a system of two non-interacting two-level systems (2LS) with opposite circular polarization selection rules (local field effect) and for the renormalized four-level system (4LS) depicted in Fig. 1 which assumes the formation of biexcitons between excitons with opposite spins. The signal strength is proportional to the strength of the local field in the case of the 2LS and to the renormalization for the 4LS. The peak signal intensities expected for pure local field and pure biexction contributions are summarized in the second and third column of Table 1 for eight experimental configurations applying different linear and circularly polarized pulses. The values are normalized to the signal strength predicted for three parallel linearly polarized pulses. Close inspection of the data reveals remarkable differences of the peak amplitude with polarization geometry for the two coupling models.

MuPAD in der Ausbildung - Postel, F.; Oevel, Gudrun; Schwarz, F. (Beiträge zum Mathematikunterricht)

Bist du's Elia? Streiflichter zum homiletischen Gebrauch der Elia-texte im 20. Jahrhundert - Schroeter-Wittke, Harald (Was suchst du hier, Elia? Ein hermeneutisches Arbeitsbuch)

Animation zum Schlafen. Predigt (Mk 4,26-29) - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Zeitroman, mimetisch. Textgeschichte, Verfahren und Status von Marieluise Fleißers ›Mehlreisende Frieda Geier‹ - Süßmann, Johannes (Literatur und Leben. Stationen weiblichen Schreibens im 20. Jahrhundert. Unter Mitarbeit v. Lena Lindhoff)

Czermak, Johannes (Hg.), Philosophy of Mathematics. Proceedings of the 15th International Wittgenstein-Symposium, 16–23 August 1992, Kirchberg am Wechsel, Austria, Part 1, Hölder-Pichler-Tempsky: Wien 1993 (= Schriftenreihe der Wittgenstein-Gesellschaft; 20/I) [Zbl. 0836.00022] - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Puhl, Klaus (Hg.), Philosophy of Mathematics. Proceedings of the 15th International Witt-genstein-Symposium, 16–23 August 1992, Kirchberg am Wechsel, Austria, Part 2, Hölder-Pichler-Tempsky: Wien 1993 (= Schriftenreihe der Wittgenstein-Gesellschaft; 20/II) [Zbl. 836.00023] - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Dependency-Based Action Refinement - Rensink, Arend; Wehrheim, Heike (Mathematical Foundations of Computer Science 1997, 22nd International Symposium, MFCS'97, Bratislava, Slovakia, August 25-29, 1997, Proceedings)

Dependency-Based Action Refinement - Rensink, Arend; Wehrheim, Heike (Mathematical Foundations of Computer Science 1997, 22nd International Symposium, MFCS'97, Bratislava, Slovakia, August 25-29, 1997, Proceedings)

Logik, Mathesis universalis und allgemeine Wissenschaft. Leibniz und die Wiederentdeckung der formalen Logik im 19. Jahrhundert - Peckhaus, Volker
Rezensionen: J. Legris, “Mathesis Universalis”, Mathesis 13 (1997), 167– 175; Zbl. Math. 884.01021 (R. Murawski); Philosophischer Literaturanzeiger 51 (1998), 114–117 (G. Schenk); MR 98h:01013 (H. Sinaceur); Peirce Project Newsletter 3 No. 1, 7; Philosophiegeschichte und logische Analyse. Logical Analysis and History of Philosophy, Bd. 2, Mentis: Paderborn 1999, 259–264 (W. Malzkorn); History and Philosophy of Logic 20 (1999), 67–69 (H. Linneweber-Lammerskitten); Erkenntnis 50 (1999), 133–136 (P. Mancosu); Berichte zur Wissenschaftsgeschichte 22 (1999), 207–208 (P. Mancosu); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin N.S. 8 (2000), H. 1, 290 (K.-H. Schlote), 49–50; Anuario Filosofico 32 (1999), 853–854; M.F., “La logica di Leibniz nel XIX secolo”, Giornale critico della filosofia Italiana 6 ser. 20 (2000), 161–164; Archiv für Geschichte der Philosophie 82 (2000), 349–352 (R. Vilkko); Epistemologia 24 (2001), 152–155 (M. Ferriani); The Review of Modern Logic 9, nos. 3 & 4 (2003–2004), 119–122 (H. Frank).

Dynamic data structures for realtime management of large geometric scenes - Fischer, Matthias; Meyer auf der Heide, Friedhelm; Strothmann, Willy-Bernhard (5th Annual European Symposium on Algorithms (ESA '97))
We present a data structure problem which describes the requirements of a simple variant of fully dynamic walk-through animation: We assume the scene to consist of unit size balls in R2 or higher dimensions. The scene may be arbitrarily large and has to be stored in secondary memory (discs) with relatively slow access. We allow a visitor to walk in the scene, and a modeler to update the scene by insertions and deletions of balls. We focus on the realtime requirement of animation systems: For some t (specified by the computation power of (the rendering hardware of) the graphic workstation) the data structure has to guarantee that the balls within distance t of the current visitor's position are presented to the rendering hardware, 20 times per second. Insertions and deletions should also be available to the visitor with small delay, independent of the size of the scene. We present a data structure that fulfills the above task in realtime. Its runtime is output-sensitive, i.e. linear in a quantity close to the output size of the query. We further present (preliminary) experimental results indicating that our structure is efficient in practice.

The anisotropic electron - positron momentum distribution in diamond - Nilen, R W N; Connell, S H; Britton, D T; Fischer, C G; Sendezera, E J; Schaaff, P; Schmidt, Wolf Gero; Sellschop, J P F; Verwoerd, W S (Journal of Physics: Condensed Matter)